An overview of the big-eyed bug fauna of French Polynesia (Heteroptera: Lygaeoidea: Geocoridae) - Kóbor, Péter (Zootaxa, 2020)
The representatives of the subfamily Geocorinae (Heteroptera: Lygaeoidea) distributed in French Polynesia are reviewed. Germalus ashlocki sp. nov. is described. First occurrence of genus Geocoris Fallén and a Germalus Stål species from New Caledonia are recorded. Diagnoses, keys and discussion of taxa are provided.